Passive recovery is superior to active recovery during a high intensity shock microcycle - Wahl, P.; Zinner, C.; Bloch, W.; Mester, J. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
In the last years there was a great scientific discussion about high intensity (interval) training (HIT). However few is known about the arrangement of interval training and its integration into the training cycle. In most cases active recovery is performed during high intensity interval training, in order to normalize lactate and pH-values and performance faster compared to passive recovery. However, recent investigations showed that lactate and pH act as signaling molecules inducing adaptations. Their time of exposure is decreased if active recovery is performed, may be leading to a decreased (metabolic) stimulus. The aim of the present study was to examine the effects of a two week high intensity shock microcycle on maximal oxygen consumption and parameters of exercise performance in junior triathletes on the one hand, and to compare the long term effects of active (A) vs. passive (P) recovery on the other hand. Methods: 16 healthy competitive junior triathletes from a local team (12 male, 4 female) participated in this study. For the assignment to the A- or P-group subjects were matched according to age and performance. Within two weeks, a total of 15 high-intensity interval sessions were performed within three 3-day training blocks. Before and one week after the last training session, athletes performed a ramp test to determine VO2max, a time trial (TT) and a Wingate-test. Furthermore total Hb-mass was determined. The results of the whole group, independent of the arrangement of recovery were analyzed at first; second the A- and P-groups were analyzed separately. Results: Peak power output (PPO) during ramp test and TT performance significantly increased in the whole group. The comparison of the two groups revealed increases for the mentioned parameters and for VO2 and power output at VT2 only for the P-group. VO2max did not change. Wingate performance increased in the A-group only. Total hemoglobin mass slightly decreased in the whole group. Discussion: The main finding of the present study was that a 14-day HIT shock microcycle is able to improve TT performance and PPO in junior triathletes in a short period of time. Furthermore, not only the intensity, but also the arrangement of interval training seems to be important as well, since only the P-group showed improvements in endurance performance, despite a slightly lower training volume. These findings might be relevant for future arrangements of high intensity interval training.